2017
DOI: 10.1039/c7sm00393e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of Shapiro-steps in colloidal monolayers driven across time-dependent substrate potentials

Abstract: We experimentally study the motion of a colloidal monolayer which is driven across a commensurate substrate potential whose amplitude is periodically modulated in time. In addition to a significant reduction of the static friction force compared to an unmodulated substrate, we observe a Shapiro step structure in the force dependence of the mean particle velocity which is explained by the dynamical mode locking between the particle motion and the substrate modulation. In this regime, the entire crystal moves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Published by IOP Publishing Ltd on behalf of the Institute of Physics and Deutsche Physikalische GesellschaftNew J. Phys. 22 (2020) 053025 N P Vizarim et alfrequency of the oscillations generated by the motion of the particle over the periodic substrate locks or comes into resonance with the ac drive frequency and its higher harmonics for a fixed range of drive intervals, producing steps in the velocity-force curves of the type found in Josephson junctions (which are known as Shapiro steps) [15,16], incommensurate sliding charge density waves [17], driven Frenkel-Kontorova systems [18], vortices in type-II superconductors moving over a periodic pinning substrate [19][20][21], and colloidal particles driven over periodic substrates [22,23]. In the case of the directional locking, there is no ac driving; however, two frequencies are still present, where one is associated with motion in the direction parallel to the drive and the other is associated with motion in the direction perpendicular to the drive.…”
mentioning
confidence: 99%
“…Published by IOP Publishing Ltd on behalf of the Institute of Physics and Deutsche Physikalische GesellschaftNew J. Phys. 22 (2020) 053025 N P Vizarim et alfrequency of the oscillations generated by the motion of the particle over the periodic substrate locks or comes into resonance with the ac drive frequency and its higher harmonics for a fixed range of drive intervals, producing steps in the velocity-force curves of the type found in Josephson junctions (which are known as Shapiro steps) [15,16], incommensurate sliding charge density waves [17], driven Frenkel-Kontorova systems [18], vortices in type-II superconductors moving over a periodic pinning substrate [19][20][21], and colloidal particles driven over periodic substrates [22,23]. In the case of the directional locking, there is no ac driving; however, two frequencies are still present, where one is associated with motion in the direction parallel to the drive and the other is associated with motion in the direction perpendicular to the drive.…”
mentioning
confidence: 99%
“…On the colloidal scale, studies of time-dependent potential energy landscapes have exhibited rich dynamics such as accelerated motion with low dispersion [35,36] and a reduction in static friction [37] due to mode locking. Conversely, time-dependence can also cause enhanced diffusion [26,27,38] and, under the correct conditions, can lead to bidirectional particle transport [39].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, time-dependence can also cause enhanced diffusion [26,27,38] and, under the correct conditions, can lead to bidirectional particle transport [39]. Experiments carried out for large systems subject to a time-dependent optical potential energy landscape show that collective effects, such as kinks, can affect the dynamics [37]. Precise control of mean drift and enhanced diffusion of colloidal particles can be achieved in traveling potential energy landscapes [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…The transport properties of passive colloidal particles have recently been shown to change when driven over one- [27][28][29][30] and two-dimensional [30][31][32][33][34] spatially periodic potential landscapes. Further complexity arises for time-dependent [35][36][37][38] and spatially random potentials [39][40][41][42][43]. Depending on the details of the driving mechanism, the use of such landscapes can result in the possibility to precisely control the speed of the net motion [28,29,36,38], the strength of diffusion [27,32,33,40] and the appearance of transport anomalies [35,37,[41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Further complexity arises for time-dependent [35][36][37][38] and spatially random potentials [39][40][41][42][43]. Depending on the details of the driving mechanism, the use of such landscapes can result in the possibility to precisely control the speed of the net motion [28,29,36,38], the strength of diffusion [27,32,33,40] and the appearance of transport anomalies [35,37,[41][42][43]. For active colloids confined by external potentials, it has been found that, in certain cases, they behave similarly to passive particles with an elevated effective temperature [44,45] or subject to an effective potential [46].…”
Section: Introductionmentioning
confidence: 99%